2016
DOI: 10.1136/jclinpath-2015-203491
|View full text |Cite
|
Sign up to set email alerts
|

The expression of arginase-1, keratin (K) 8 and K18 in combined hepatocellular-cholangiocarcinoma, subtypes with stem-cell features, intermediate-cell type

Abstract: Arg-1 and K8 were good markers to identify intermediate cells between hepatocytes and cholangiocytes. These can be useful markers for pathological diagnosis of CHC-INT, which usually has wide histological diversities, in combination with other hepatocytic and/or cholangiocytic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Moreover, there was no case with a HepPar‐1 score ≥4 in INT. Similarly, in a study by Akiba et al ., which did not take into account the expression intensity of immunostaining, as few as 28.1% of INTs were HepPar‐1 positive and there are arguably not many cases where INTs showed strong expression of HepPar‐1. Our results showed that a case with a HepPar‐1 score ≥2 could be diagnosed as HCC with high sensitivity (93.3%) and high specificity (96.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was no case with a HepPar‐1 score ≥4 in INT. Similarly, in a study by Akiba et al ., which did not take into account the expression intensity of immunostaining, as few as 28.1% of INTs were HepPar‐1 positive and there are arguably not many cases where INTs showed strong expression of HepPar‐1. Our results showed that a case with a HepPar‐1 score ≥2 could be diagnosed as HCC with high sensitivity (93.3%) and high specificity (96.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Akiba et al . previously demonstrated that arginase‐1 and keratin (K) 8 are useful for the pathological diagnosis of INT . However, no specific markers of INT have been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…At the current time, there are no published consensus guidelines for minimum amounts of HCC or iCCA to qualify for the diagnosis, either in biopsy material or in resected/explant samples. Examples have been illustrated . In regions in which the tumors seem to merge, the cellular morphology may be difficult to identify as either hepatocellular or cholangiocytic by pure H&E evaluation alone.…”
Section: Microscopic Pathologymentioning
confidence: 99%
“…Examples have been illustrated. (7)(8)(9)(18)(19)(20)(21)(22) In regions in which the tumors seem to merge, the cellular morphology may be difficult to identify as either hepatocellular or cholangiocytic by pure H&E evaluation alone. Tumor cells of either hepatocytic or cholangiocytic morphologic type may contain intracytoplasmic inclusions common to hepatocytes such as Mallory-Denk bodies, steatosis, a1AT globules (even in an a1AT genotypically normal individual), fibrinogen, etc.…”
Section: Microscopic Pathologymentioning
confidence: 99%
“…In particular, the histopathological findings of rare (ii) CHC-INT characteristically demonstrate a proliferation of relatively small and uniform carcinoma cells having intermediate features between hepatocytes and cholangiocytes, i.e., HCC and CCC, arranged in strands, solid nests, trabeculae, and/or ill-defined gland-/tubule-like structures [ 4 ]. A substantial number of interesting papers focusing especially on the histopathological and immunohistochemical features of CHC-INT were published [ 3 , 5 ]; however, within our thorough investigation, there has been no detailed description regarding the gross findings reported in the English literature. Indeed, the above WHO classification has merely stated that the gross morphology of CHC-INT is not significantly different from that of HCC [ 4 ]; however, we cannot completely agree with that description.…”
Section: Introductionmentioning
confidence: 99%